Pengembangan Video Pembelajaran Desain Grafis untuk Buku Digital Interaktif bagi Siswa Tunarungu - Mursalat Mursalat; Eveline Siregar; Indina Tarjiah (Jurnal Paedagogy, 2023)
This research aims to develop graphic design learning videos for interactive digital books for deaf students. This development is intended to complement visual material in digital books as teaching materials specifically designed according to student characteristics. The subject being developed was graphic design at the high school level in special education schools. The method used in this study was research and development with SAM (Successive Approximation Model). The validation included media, material (content), learning, and language. This data analysis technique used quantitative descriptive research. This research data analysis technique used quantitative descriptive. The study results showed that the learning videos that had been developed could aid in the understanding of theory as an abstract for the deaf with explanations of text, infographics, and sign language in the video. Sign language expressions made students interested and motivated to learn. The results of the validity evaluation by experts from the media aspect were 76%, Very Feasible, no need for revision and content 76%, Very Feasible, no need for revision; learning aspects 79%, Very Feasible, no need for revision; language 82%, Very feasible, no need revision. The summary score of experts and students was 78%, which was Very feasible, and did not need to be revised.